2008
DOI: 10.1111/j.1728-4457.2008.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

On Postponement and Birth Intervals

Abstract: Much of the literature on fertility transition presumes that women birth control is practiced either to limit family size or to space births. This paper argues that women also use contraception to postpone pregnancy. Postponement is not synonymous with spacing. It arises when women delay their next birth for indefinite periods for reasons unrelated to the age of their youngest child, but without deciding not to have any more children. Postponement has a distinctive impact on the shape of birth interval distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 44 publications
(38 reference statements)
9
79
0
Order By: Relevance
“…Among the subpopulations where the longest times to next birth have emerged, the changes in duration-specific fertility schedules strongly suggest that postponement was the most common motive for birth control, particularly in Zimbabwe. In this sense, the Modelling fertility in Eastern Africa 13 results of this study largely support Timaeus and Moultrie's (2008) assertion that fertility transition in sub-Saharan Africa is seeing the emergence of very long birth intervals, which cannot readily be accounted for by birth spacing as it is usually envisaged. However, fertility in Eastern Africa is changing in a more complex way than any of the current literature suggests.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Among the subpopulations where the longest times to next birth have emerged, the changes in duration-specific fertility schedules strongly suggest that postponement was the most common motive for birth control, particularly in Zimbabwe. In this sense, the Modelling fertility in Eastern Africa 13 results of this study largely support Timaeus and Moultrie's (2008) assertion that fertility transition in sub-Saharan Africa is seeing the emergence of very long birth intervals, which cannot readily be accounted for by birth spacing as it is usually envisaged. However, fertility in Eastern Africa is changing in a more complex way than any of the current literature suggests.…”
Section: Discussionsupporting
confidence: 73%
“…The height of the distribution does not change because women's preferences for a particular family size have not changed, as shown by the dotted line in Figure 1 (Timaeus and Moultrie 2008). Third, the distribution produced in a hypothetical population in which women intend to postpone their next birth for an initially indefinite period shows lower fertility at shorter durations since the previous birth and higher fertility at longer durations than the base distribution (also shown in Figure 1).…”
Section: Modelling Different Strategies Of Birth Controlmentioning
confidence: 93%
See 1 more Smart Citation
“…We have shown that this trend of lengthening is seen even when only closed birth intervals are included in the analysis. This phenomenon has been observed in a number of other studies, including those of Moultrie and colleagues (Moultrie, Sayi, and Timaeus 2012;Timaeus and Moultrie 2008) and Casterline and colleagues (Bongaarts and Casterline 2012;Casterline and Odden 2016). Despite a recent decrease in the reported length of intervals in Zimbabwe, both conditional and unconditional median birth intervals at the national level are longer in Zimbabwe than in Ethiopia, Kenya, and Tanzania.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, Lightbourne (1985) shows that in World Fertility Surveys (WFS), even after birth intervals longer than five years, many women report wanting neither to stop childbearing nor to space a birth, but still report desiring to delay their next conception. We question the traditional demographic presumption that the open birth intervals of limiters are qualitatively different from the closed intervals of non-limiters (Cleland and Rutstein 1986;Timaeus and Moultrie 2008).…”
Section: Methodsmentioning
confidence: 99%